PARTISIPASI PUBLIK DALAM PEMBENTUKAN PERATURAN DAERAH DI KABUPATEN POHUWATO - Marwan Marwan (AkMen JURNAL ILMIAH, 2016)
The purpose of this study was to determine the mechanism or process of forming local laws in providing space for public participation in the District Pohuwato and to find out what factors are an obstacle to public participation in the establishment of local regulations in Pohuwato. While the results of this study is the space for public participation in the establishment of local regulations do not clearly regulated and public participation only at the hearing (public hearing) the board members meet with the community to conduct public consultation. Stages of public participation in the establishment of the Regional District Regulation Pohuwato still at the level of consultation and has not reached the strength of a society where government authority sebahagian submitted to the public in the process of formation of local regulation. Factors that become an obstacle to public participation in the Regional Regulation on Establishment of District Pohuwato are, first, the lack of accessible information, second, existence of order in the Legislative Assembly as an inhibiting factor, because people are present only at the invitation during the discussion of regulatory area, although there is a desire sebahagian community to attend, but due to limited invitation only and those who attended the invitation did not have voting rights as participants in the meeting. Third, lack of desire or arrange for the affairs of society itself, as one of the factors inhibiting public participation, and they only carry out just what has been created by a board member.